How service quality and outcome confidence drive pre-outcome word-of-mouth - Ifie, Kemefasu; Simintiras, Antonis C.; Dwivedi, Yogesh; Mavridou, Vasileia (Journal of retailing and consumer services, 2018)
Existing research on word-of-mouth (WOM) referrals has rarely considered what drives consumers to engage in pre-outcome WOM (i.e., referrals before they have experienced the final service outcome). This study argues that WOM behavior that predates the service outcome is driven by the interplay between present experience (perceived quality of the service process) and anticipations of the future outcome (outcome confidence). Drawing upon perceived risk theory, the study explores how outcome confidence and service process quality independently predict WOM behavior and how outcome confidence moderates the impact of process quality on WOM behavior. We investigate these issues with customers of a driving school and use a multilevel modelling approach to test the hypotheses. The results show that consumers with higher levels of outcome confidence are more willing than low-confidence consumers to transmit pre-outcome WOM. However, the study also finds that outcome confidence compensates for process quality such that the effect of process quality diminishes when outcome confidence is high. The key managerial implication of the study's finding is that managers can tactically use outcome confidence to compensate for low levels of process or employee service quality.